GUEST SATISFACTION DITINJAU DARI SERVICE, FACILITIES, GREEN IMAGE, AND PRICE, IN HOTEL INDUSTRY - I Ketut Sirna; Ni Komang Samiasti; I Nyoman Tri Sutaguna (Majalah Ilmiah Widyacakra, 2020)
ABSTRACTThis research was conducted at Semabu Hills Hotel, which is the first hotel as a 3-star hotelin Nusa Penida. This study is to determine Guest satisfaction in terms of service, facilities,green image and price at Semabu Hills Hotel Nusa Penida. This study used accidentalsampling with 115 respondents. Collecting data by means of observation, documentation,interviews and questionnaires. The method of analysis used statistical tests, multiple linearregression tests, and hypothesis testing t test and f test. The results of this study partially findthat service has a positive effect on guest satisfaction at Semabu Hills Hotel, in terms ofmultiple linear regression of 0.171, and is strengthened by the t value is more than the t table,namely 3,420> 1,981. Facilities have a positive and significant effect on guest satisfaction atSemabu Hills Hotel, using multiple linear regression of 0.151 and reinforced by the t value ismore than the t table, namely 3.505> 1.981. Green Image has a positive and significant effecton guest satisfaction at Semabu Hills Hotel, using linear regression with a difference of0.190, and it is strengthened by the t value of more than t table 3.183> 1.981. Price has apositive and significant effect on guest satisfaction at Semabu Hills Hotel, using multiplelinear regression of 0.249, and is strengthened by the t value of more than t table 3.038>1.981. While Service, Facilities, Green Image and Price simultaneously have a positive andsignificant effect on Guest Satisfaction at Semabu Hills Hotel, this can be seen in theregression equation Y = 1,440 + 0.171b1 + 0.151b2 + 0.190b3 + 0.249b4, and strengthenedby the value f count more than f table 49.448> 2.69. and simultaneously the results of theDetermination test are 63% and the remaining 37% are determined from other variables thathave not been examined in this study. From this research it can be concluded that there is apositive and significant influence between Service, Facilities, Green Image, and Price eitherpartially or simultaneously on Guests Satisfaction at Semabu Hills Hotel Nusa Penida.